2017
DOI: 10.5039/agraria.v12i4a5473
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and nutrient concentration in spineless cactus under different fertilizations and plant densities

Abstract: The objective was to evaluate the productivity and nutrient concentration in spineless cactus 'Miúda' (Nopalea cochenillifera Salm Dyck) under levels of nitrogen (N) fertilization (0, 150, 450 and , nitrogen fertilization did not affect productivity, however, there was a linear increase in plots with 40,000 ha -1 plants. The plant N concentration increased with nitrogen fertilization and ranged from 7.3 to 9.9 g kg -1. The plant phosphorus (P) concentration was influenced by the interaction between all the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 8 publications
(11 reference statements)
0
7
1
Order By: Relevance
“…These authors obtained the highest green matter production per hectare at 330 days after planting (92.79 t), evaluating different population arrangements and phosphorus doses. The yield obtained in the present study was 4 times higher than that reported by Souza et al (2017), who worked with 'Miúda' prickly pear at density of 40,000 thousand plants per hectare.…”
Section: Resultscontrasting
confidence: 77%
“…These authors obtained the highest green matter production per hectare at 330 days after planting (92.79 t), evaluating different population arrangements and phosphorus doses. The yield obtained in the present study was 4 times higher than that reported by Souza et al (2017), who worked with 'Miúda' prickly pear at density of 40,000 thousand plants per hectare.…”
Section: Resultscontrasting
confidence: 77%
“…Thus, the greater plant height with the WH treatment can been explained due to the lower number and area of cladodes obtained with this treatment. Cactus pears with greater cladode development and more cladodes tend to have a lower plant height [ 37 , 38 ], which was what happened with the hydrogel treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental factors such as rainfall play an important role in some variables of cactus pear (e.g., DM concentration) because evapotranspiration potential presents a relationship with air temperature most times of the year (Souza et al., 2017), promoting a considerable water deficit in soils of arid and semiarid regions (Chiacchio et al., 2006). Even though the cactus pear is adapted to this condition, a high‐water deficit could affect cactus performance.…”
Section: Discussionmentioning
confidence: 99%
“…In the semiarid region, forage production is limited, mainly due to great evapotranspiration rate and limited rainfall (Marques et al., 2020; C. Santos et al, 2017). Evapotranspiration potential has a relationship with air temperature and seasons of the year (Souza et al., 2017), promoting a considerable water deficit in soils of arid and semiarid regions (Chiacchio et al., 2006). It is important to mention that aridity index (AI) is a numerical indicator of aridity based on long‐term climatic water deficits and it is calculated as the ratio between precipitation and potential evapotranspiration; thus, in semiarid regions the AI is 0.2 ≤ AI ≤ 0.5 (Middleton & Thomas, 1997; Nouri et al, 2019).…”
Section: Introductionmentioning
confidence: 99%